Disparate effects on renal and oxidative parameters following RAGE deletion, AGE accumulation inhibition, or dietary AGE control in experimental diabetic nephropathy - Tan, Adeline L. Y.; Sourris, Karly C.; Harcourt, Brooke E.; Thallas-Bonke, Vicki; Penfold, Sally; Andrikopoulos, Sofianos; Thomas, Merlin C.; O'Brien, Richard C.; Bierhaus, Angelika; Cooper, Mark E.; Forbes, Josephine M.; Coughlan, Melinda T. (American journal of physiology. Renal physiology, 2010)
Advanced glycation end products (AGEs) and the receptor for AGEs (RAGE) generate ROS, and therefore this study evaluated the effects of RAGE deletion, decreasing AGE accumulation, or lowering dietary AGE content on oxidative parameters in diabetic nephropathy (DN). Control and diabetic male wild-type and RAGE-deficient (RAGE−/−) mice were fed high- or low-AGE diets, with two groups given the inhibitor of AGE accumulation, alagebrium chloride, and followed for 24 wk. Diabetic RAGE−/− mice were protected against albuminuria, hyperfiltration, glomerulosclerosis, decreased renal mitochondrial ATP production, and excess generation of both mitochondrial and cytosolic superoxide. Whereas glomerulosclerosis, tubulointerstitial expansion, and hyperfiltration were improved in diabetic mice treated with alagebrium, there was no effect on urinary albumin excretion. Both diabetic RAGE−/− and alagebrium-treated mice had an attenuation of renal RAGE expression and decreased renal and urinary AGE (carboxymethyllysine) levels. Low-AGE diets did not confer renoprotection, lower the AGE burden or renal RAGE expression, or improve cytosolic or mitochondrial superoxide generation. Renal uncoupling protein-2 gene expression and mitochondrial membrane potential were attenuated by all therapeutic interventions in diabetic mice. In the present study, diverse approaches to block the AGE-RAGE axis had disparate effects on DN, which has potential clinical implications for the way this axis should be targeted in humans.